Visualizing the soundscape of the calving grounds of the North Atlantic Right Whale - Towsey, Michael; Barclay, Leah; Brock, Ginna (Australian Association of Writing Programs, 2018)
The key to this provocation is the spectrogram with its beautiful bands of colours. This image represents 44 days of recorded acoustic data which has been subject to falsecolour imagery in the same way that satellite images are represented. The soundscape was captured to help ecologists understand the migration patterns of the endangered North Atlantic Right Whale. The spectrograms identify three dominant features of the ocean soundscape in the area of this sample (15 kilometres off the coast of Georgia in the centre of the whales’ calving grounds): mechanical noise from passing ships; the night chorus of the black-drum fish (Pogonias cromis); and a mysterious third element, possibly caused by the cables that tether the hydrophone to the ocean floor strumming under the influence of strong tidal currents.